(untitled) (Palestine Issues on Indonesian Society, 2025)
This paper analyzes the discourse surrounding Palestinian struggles in Indonesian Friday sermons, focusing on how religious leaders use their platforms to discuss the Palestinian cause. Using a qualitative discourse analysis of sermons delivered across mosques in Indonesia, the study investigates how Palestinian issues are framed in terms of Islamic solidarity, resistance, and justice. The paper explores the rhetorical strategies employed by Islamic clerics, examining how religious narratives intersect with political advocacy, religious duty, and international solidarity. In particular, it identifies how Friday sermons serve as a space for the intersection of religious teachings with global political concerns, including discussions of human rights violations and the occupation of Palestinian territories. This study finds that while Indonesian religious leaders frequently emphasize the moral and theological aspects of supporting Palestine, there is also a notable shift toward politically charged messages that align with Indonesia’s broader foreign policy objectives. The research sheds light on the role of religious institutions in shaping public opinion on international issues, as well as the importance of religious discourse in mobilizing political activism within Muslim-majority societies.